Construction of Law Regarding The Role of The Regional Government In Providing Incentives For Micro Businesses Through Equity Crowdfunding - Shinta Puspita Sari (SASI, 2023)
Introduction: The policy complementary to regional investment is governed in Article 278 of Law Number 23 of 2014 and Government Regulation Number 24 of 2019. The availability of incentives and supporting facilities, however, remain to be the problems amidst shrinking regional budgets following the pandemic affecting economic sectors. The Regional Government of Batu City, among others, has perceived this effect and is on its way to reviving micro businesses to back up the local tourism.